FUTURE PROJECTIONS OF UZBEKISTAN'S ECONOMIC RECOVERY AFTER THE PANDEMIC - Tuychiev Inoyatillo (Research Parks Publishers, 2020)
The novel coronavirus (COVID-19) is challenging the world. With no vaccine available and only partial medical capacityto treat the virus, no pharmaceutical interventions (NPI) are the primary strategy to contain the pandemic. Unprecedented global travel restrictions and stay-at-home orders are causing the most severe disruption of the global economy since World War II. The paper brings some statistics on the current situation and discuss economic recoveries after the earlier crisis caused by epidemics as SARS, H1N1, and MERS. It explores the ongoing situation in Uzbekistan and provides a future forecast on the country's economy during the post-pandemic period.